Racial/ethnic disparities in early‐onset colorectal cancer: implications for a racial/ethnic‐specific screening strategy. (28th February 2021) - Acuna‐Villaorduna, Ana R.; Lin, Juan; Kim, Mimi; Goel, Sanjay
Abstract: Introduction: Early‐onset colorectal cancer (EO‐CRC) is a public health concern. Starting screening at 45 years has been considered, but there is discrepancy in the recommendations. Racial disparities in EO‐CRC incidence and survival are reported; however, racial/ethnic differences in EO‐CRC features that could inform a racial/ethnic‐tailored CRC screening strategy have not been reported. We compared features and survival among Non‐Hispanic White (NHW), Non‐Hispanic Black (NHB), and Hispanics with EO‐CRC. Methods: CRC patients from SEER 1973–2010 database were identified, and EO‐CRC was defined as CRC at <50 years. Clinical/pathological features and survival were compared between NHW, NHB, and Hispanics. Cancer‐specific survival (CSS) predictors were assessed in a multivariable Cox proportional hazard model. Results: Of 166, 416 patients with CRC, 16, 545 (9.9%) had EO‐CRC. The EO‐CRC frequencies in NHB and Hispanics were higher than NHW (12.7% vs. 16.5% vs. 8.7%, p < 0.001). EO‐CRC in NHB presents more frequently in females, with well/moderately differentiated, stage IV, and is less likely to present in locations targetable by sigmoidoscopy than NHW (54.6% vs. 67.7% OR:1.7, 95% p < 0.001). 5‐year CSS was lower in NHB (59.4% vs. 72.8%, HR: 1.7; 95% CI: 1.54–1.82) and Hispanics (66.4% vs. 72.8%, HR: 1.3; 95% CI: 1.16–1.39) than NHW. A regression model among patients with EO‐CRC showed that being NHB or Hispanic were independent predictors for cancer‐specific mortality, after adjusting for gender, grade, stage, and surgery. Conclusion: EO‐CRC is more likely in NHB and Hispanics. Racial disparities in clinical/pathological features and CSS between NHB and NHW/Hispanics were evidenced. A racial/ethnic specific screening strategy could be considered as an alternative for patients younger than 50 years. Abstract : An alarming increase in the incidence of early‐onset colorectal cancer (EO‐CRC) has prompted updates in CRC screening guidelines; however, consensus has not been reached yet. Early‐onset colorectal cancer (EO‐CRC) presents more frequently in racial minority groups compared to Non‐Hispanic Whites (NHW). Compared to NHW/Hispanics, EO‐CRC in NHB presents more frequently in females, with a higher rate of well/moderately differentiated, advanced staged and right‐sided tumors. A race‐tailored CRC screening strategy including full colonoscopy in NHB and sigmoidoscopy in NHW and Hispanics could represent a cost‐effective method for screening in young population.